O perdão interpessoal em situações de injustiças da vida cotidiana - Campos, Sammya Gabryella Soares Pereira (2023)
The literature indicates that studies about forgiveness are directed to contexts of relationships in the family, among friends, intimate partners and relationship contexts at work. However, themes that work in everyday social contexts are not so explored by the literature. And, it is important to emphasize that injustices can occur in our daily lives regardless of the type and/or intensity of a relationship, for example, the relationship between a student/teacher, co-workers, neighbors and even strangers. In this sense, this study aimed to analyze the degrees of interpersonal forgiveness in relationships in which affective bonds are non-existent and to verify the relationship with anger and anxiety. To achieve this goal, we carried out a field research, quantitative, descriptive and correlational and 359 people participated in the study, 273 (76%) women and 86 (24%) men, selected through non-probabilistic convenience sampling. For data collection, carried out online and face-to-face, we used: sociodemographic questionnaire, injustice questionnaire, Anger Expression Inventory (STAXI), State and Trait Anxiety Inventory (STAI) and the Enright Forgiveness Scale (EFI). For the analysis, the data were received in an excel spreadsheet and then transferred to the IBM 22.0. Considering the sample of people who felt very or tremendously hurt (hurt > 3), the results indicated that this population forgave more offenses of racial discrimination and political differences and the hurt was felt more intensely when the offense was caused by unknown people or by professionals. We also found that people with hurt > 3 forgive significantly less than people who felt little hurt (hurt < 3). In the correlation of people with hurt > 3, we found that very hurt people with traits of anger tend to show negative affect and not judge the offender positively, partially confirming hypothesis 1. In this same sample, we found that people with traits of anxiety tend to show absence of negative behaviors (greater vindictive behavior), which corroborates the literature studied, also partially confirming the hypothesis. Comparing means between state and trait anxiety and state and trait anger in the hurt sample > 3, we noticed that the degrees of anxiety were significantly higher than the degrees of anger.